Extremely Low Frecuency (ELF) Electromagnetic Radiation Potential To Accelerate Fracture Splicing - Sudarti; Sri Septi Dyah Pratiwi (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
The treatment process for healing fractures in the community is still mostly done through traditional methods, which are generally referred to as "sangkal putung". The results obtained 28.2% can not return to its original form. In the process of denying putung it still takes quite a long time depending on the part of the bone that has broken. This study aims to reveal the potential effect of exposure to the ELF (Extremely Low Frequency) magnetic field on the fracture healing process. This research method uses an article review, with a total of 30 articles from relevant research articles from 2000 to 2022. This aims to examine the effect of effective treatment of the intensity of exposure to the ELF magnetic field on the fracture healing process. The results showed that there were 73.3% of researchers who supported the ELF EM wave was able to accelerate the splicing of fractures. Meanwhile, 26.67% of researchers did not support it. The results of the study reported that exposure to a magnetic field with an intensity of 120μT-200μT was able to increase the proliferation of osteoblast cells so as to heal fractures. The most accurate range of intensity in the process of forming Osteoblam cells is the intensity of 150μT. The results in experimental animals showed that exposure to the ELF magnetic field had an effect on the process of forming osteoblasts completely. The results of clinical research (bone fracture patients) showed that exposure to a magnetic field with an intensity of 150μT was able to form and secrete organic collagen and non-collagen in Osteoblast cells, while ELF Osteoclast cells were able to assist in the reabsorption of existing bone cells. Based on the results of the analysis, it can be concluded that exposure to the 150μT intensity ELF magnetic field has the most optimal ability in the process of forming osteoblasts (osteoclasts and osteosts) in fracture healing.